2021
DOI: 10.3390/en14010206
|View full text |Cite
|
Sign up to set email alerts
|

Sweet Drinks as Fuels for an Alkaline Fuel Cell with Nonprecious Catalysts

Abstract: Sugar has the potential to create enough energy to power mobile electronics. Various sugar-powered fuel cells have been reported, however, most of them used pure glucose as substrate and enzymes/noble metals as catalysts. In this work, an alkaline fuel cell with cheap catalysts were constructed, and different sweet drinks were used as fuels for power generation. The influence of different substrates on the electrochemical performance was characterized under the controlled conditions. Our experimental results s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Comparison of fuel cells with other power-generating systems [11]. According to the choice of fuel and electrolyte, fuel cells are categorised into six major groups: (1) alkaline fuel cell (AFC) [12], (2) phosphoric acid fuel cell (PAFC) [13],…”
Section: Introductionmentioning
confidence: 99%
“…Comparison of fuel cells with other power-generating systems [11]. According to the choice of fuel and electrolyte, fuel cells are categorised into six major groups: (1) alkaline fuel cell (AFC) [12], (2) phosphoric acid fuel cell (PAFC) [13],…”
Section: Introductionmentioning
confidence: 99%
“…Rahman et al (2021) reported the generation of 483.5 mV from the use of this substrate in an MFC, and this result was associated with the high availability of glucose as an energy source for microorganisms so that sugars such as glucose are easily metabolized by a wide range of microbes, for which it has been shown that this substrate is a beneficial fuel for bioelectricity generation in an MFC [20][21][22]. In this sense, sugars such as glucose and sucrose have several advantages because they are low cost, easy to obtain, and sustainable since they can be easily produced in a natural environment, so a source that provides large amounts of sugars as organic waste from food industries is fruit processing plants [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, there are no explosion hazards or storing problems associated with glucose, while hydrogen and methanol are very flammable and can cause fires and explosions when being handled improperly. These advantages make GFCs a promising source for sustainable energy and has attracted great attention from global researchers and institutions [14,18,19,21,22].…”
Section: Introductionmentioning
confidence: 99%